2018
DOI: 10.3390/jcm7040078
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Radiological Results of Proximal Femoral Nail Antirotation (PFNA) Osteosynthesis in the Treatment of Unstable Pertrochanteric Fractures

Abstract: Pertrochanteric femur fractures are considered amongst the most commonly encountered fractures in the geriatric age group. We evaluated radiographic and functional outcomes of patients with unstable pertrochanteric fractures treated with the proximal femur nail antirotation (PFNA). Between March 2013 and December 2015, fifty patients (28 male and 22 females with a mean age of 72.8 years (range, 20–94)) with unstable pertrochanteric fractures (AO 31.A2 and 31.A3) were fixed with the PFNA at our institution, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
2
23
0
2
Order By: Relevance
“…We got satisfactory results with PFNA-2, and there was no considerable difference between 2 groups in terms of functional outcome. e varus collapse was seen in 12% [18], 5.8% [21], and 4.9% [22] of cases in previous studies. We got 15% cases with varus collapse with screw back out in the lateral entry group.…”
Section: Advances In Orthopedicsmentioning
confidence: 57%
See 2 more Smart Citations
“…We got satisfactory results with PFNA-2, and there was no considerable difference between 2 groups in terms of functional outcome. e varus collapse was seen in 12% [18], 5.8% [21], and 4.9% [22] of cases in previous studies. We got 15% cases with varus collapse with screw back out in the lateral entry group.…”
Section: Advances In Orthopedicsmentioning
confidence: 57%
“…PFNA has been advised in elderly patients, and studies have found it to be a better implant and has given satisfactory functional and radiological results with minimal complications [18][19][20]. We got satisfactory results with PFNA-2, and there was no considerable difference between 2 groups in terms of functional outcome.…”
Section: Advances In Orthopedicsmentioning
confidence: 61%
See 1 more Smart Citation
“…In the aged population, intertrochanteric fractures, leading to severe functional impairments, are one of the most frequent fractures; besides, it has become a severe health issue due to the rapid increase in the aged population in recent years [1][2][3][4]. Some studies reported that the annual incidence of hip fractures exceeds 320,000 cases in North America, and by 2050, this number is projected to rise to 6 million with an average annual mortality rate of more than 20% for hip fractures and intertrochanteric fractures; besides, in 2011, 316,000 hip fracture patients in the United States were hospitalized for $ 4.9 billion, while in the United Kingdom, Wales and Northern Ireland, national health services for hip fracture patients cost up to £ 1 billion [5].…”
Section: Introductionmentioning
confidence: 99%
“…PFNA has a large area of spiral blade, which can achieve tighter bone compaction and femur alignment than traditional screws, providing optimal anchoring and stability for intertrochanteric fractures, thus effectively preventing femoral head/neck rotation and the varus collapse, especially in patients with osteoporosis [9][10][11]. Indeed, more research 4 works related to femoral intertrochanteric fractures have demonstrated that PFNA is associated with smaller incisions, lower complication rates, and shorter length of stay compared to dynamic hip screws [2]. In addition, InterTAN nail, as another type of intramedullary fixation, uses an integrated interlocking lag nail system in which the main tension screw and the compression screw are trapezoidal in outline.…”
Section: Introductionmentioning
confidence: 99%